1988
DOI: 10.1210/jcem-67-6-1278
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Corticotropin-Releasing Hormone Binding Protein in Human Plasma by Chemical Cross-Linking and its Binding during Pregnancy*

Abstract: A human plasma CRH-binding protein (CRH-BP) was identified and characterized by chemical cross-linking of 125I-Tyr-hCRH to human plasma using disuccinimidyl suberate. The apparent mol wt of the cross-linked complex determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis followed by autoradiography was approximately 43,000. The mol wt was slightly lower in the nonreduced state, suggesting the presence of intramolecular disulfide bonds. Subtracting the mol wt of 125I-Tyr-CRH, the BP appeared to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
5

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 19 publications
1
34
0
5
Order By: Relevance
“…Detection of plasma ACTH in spite of the significant increase of plasma-free cortisol during pregnancy may support this hypothesis. Second, the bound CRH to CRH binding protein still has bioactivity (16). Third, maternal plasma CRH levels did not show any significant variation during a 3-h observation when plasma samples were obtained at 20-min intervals in late pregnancy (Sasaki, A., unpublished observations); in contrast, plasma CRH after a bolus injection of synthetic rat CRH was rapidly eliminated from peripheral plasma (17).…”
Section: Discussionmentioning
confidence: 97%
“…Detection of plasma ACTH in spite of the significant increase of plasma-free cortisol during pregnancy may support this hypothesis. Second, the bound CRH to CRH binding protein still has bioactivity (16). Third, maternal plasma CRH levels did not show any significant variation during a 3-h observation when plasma samples were obtained at 20-min intervals in late pregnancy (Sasaki, A., unpublished observations); in contrast, plasma CRH after a bolus injection of synthetic rat CRH was rapidly eliminated from peripheral plasma (17).…”
Section: Discussionmentioning
confidence: 97%
“…Corticotropin releasing factor-binding protein (CRF-BP) is a 37-kDa glycoprotein that was originally found to circulate in high concentrations in late gestational maternal plasma where it likely prevents inappropriate release of ACTH from the pituitary gland by placental-derived CRF (13)(14)(15). CRF-BP was named for its ability to bind to CRF with high affinity (16), but it also binds to other members of the CRF family of neuropeptides.…”
Section: Corticotropin Releasing Factor (Crf)mentioning
confidence: 99%
“…Suds et al (11) reported that the levels of CRH binding protein Data reported by other investigators on the forms of human placental CRH-IR have not been consistent, with findings of two (2, 3) and three (13) larger molecular weight forms. Sasaki et al using Sephadex G-75 chromatography, described two peaks of CRH-IR in human placental extracts (2), a result replicated by Cunnah et al (3) using similar conditions.…”
Section: Large Crh-ir Is Bioactive 97mentioning
confidence: 91%